2015
DOI: 10.1159/000438572
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of MicroRNA-100 in Human Cancer and its Therapeutic Potential

Abstract: MicroRNAs (miRNAs) are a recently discovered class of endogenous, small (about 22 nucleotides) non-coding RNAs, which play important roles in cancer development and progression. Emerging evidence shows that microRNAs exert their regulatory effects by directly binding to the 3'- untranslated regions (UTRs) of their target genes. MicroRNA-100 (miR-100) is aberrantly expressed and functions in many human cancers by regulating multiple cell processes, such as cell cycle, proliferation, differentiation, migration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 150 publications
(151 reference statements)
1
55
0
2
Order By: Relevance
“…It is involved in regulating multiple cell processes, such as cell apoptosis, cell cycle, differentiation, proliferation, invasion, and migration. 25,26 miR-100 was reported to enhance the chemosensitivity of various tumor cells to chemotherapeutics. 27,28 Several researches proved that overexpression of miR-100 can sensitize cancer cells to DDP in various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in regulating multiple cell processes, such as cell apoptosis, cell cycle, differentiation, proliferation, invasion, and migration. 25,26 miR-100 was reported to enhance the chemosensitivity of various tumor cells to chemotherapeutics. 27,28 Several researches proved that overexpression of miR-100 can sensitize cancer cells to DDP in various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have reported that miR-210 plays an important role in the development of various types of cancer by regulating tumorigenesis and tumor growth, and miR-210 has been shown to exert its functions under hypoxic conditions [45, 46]. A variety of hypoxic reactions that affect tumor generation are mediated by hypoxia-inducible factor (HIF).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms that have been extensively investigated at both levels of genes and proteins would contribute to improve the clinical treatment [98]. Several reports have shown that miR-129-based therapeutics could help to achieve the multitargeted anticancer therapeutic strategy.…”
Section: Mir-129 As a Therapeutic Target For Human Cancersmentioning
confidence: 99%